Assessing the Spread and Uptake of a Framework for Introducing and Evaluating Advanced Practice Nursing Roles. Issue 4 (13th April 2016) - Boyko, Jennifer A.; Carter, Nancy; Bryant‐Lukosius, Denise
ABSTRACT: Background: Health system researchers must ensure that the products of their work meet the needs of various stakeholder groups (e.g., patients, practitioners, and policy makers). Evidence‐based frameworks can support the uptake and spread of research evidence; however, their existence as knowledge translation tools does not ensure their uptake and it is difficult to ascertain their spread into research, practice, and policy using existing methods. Purpose: The purpose of this article is to report results of a study on the spread and uptake of an evidence‐based framework (i.e., the participatory, evidence‐based, patient‐focused process for advanced practice nursing [PEPPA] framework) into research, practice, and policies relevant to the introduction and evaluation of advanced practice nursing roles. We also reflect on the utility of using a modified citation methodology to evaluate knowledge translation efforts. Methods: We searched four databases for literature published between 2004 and 2014 citing the original paper in which the PEPPA framework was published, and carried out an Internet search for grey literature using keywords. Relevant data were extracted from sources and organized using NVivo software. We analysed results descriptively. Results: Our search yielded 164 unique sources of which 69.5% were from published literature and the majority (83.4%) of these were published in nursing journals. Most frequently (71.5%), the framework was used by researchers and students in research studies. A smaller number of citations (11.3%) reflected use of the PEPPA framework in practice settings with a focus on role development, implementation, evaluation, or a combination of these. Linking Evidence to Action: This study demonstrates that the PEPPA framework has been used to varying degrees as intended, and provides guidance on how to evaluate the spread and uptake of research outputs (e.g., theoretical frameworks). Further research is needed about ways to determine whether evidence‐informed research tools such as frameworks have been taken up successfully into practice and policy contexts.